2013
DOI: 10.1136/bcr-2013-009467
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the parotid gland: a rare entity

Abstract: SUMMARYPrimary squamous cell carcinoma of the parotid gland is a rare aggressive malignancy. It is a rapidly advancing lesion which, if not recognised and treated early, results in high morbidity and mortality. Despite radical surgery and adjuvant radiotherapy, prognosis of this cancer continues to be poor. Careful clinical and histological examination is mandatory to differentiate this tumour from metastatic squamous cell carcinoma and other primary malignancies of the parotid. The authors hereby report the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…What is more, in our study we decided to exclude patients with squamous cell carcinoma as it mostly represents metastatic skin cancer rather than a primary salivary gland malignancy. 6 Distant recurrence was the most common pattern of failure in our study. Multiple reports revealed that it actually ranged from 11.1% to 52% of cases constituting the most likely reason for poor outcome.…”
Section: Discussionmentioning
confidence: 52%
“…What is more, in our study we decided to exclude patients with squamous cell carcinoma as it mostly represents metastatic skin cancer rather than a primary salivary gland malignancy. 6 Distant recurrence was the most common pattern of failure in our study. Multiple reports revealed that it actually ranged from 11.1% to 52% of cases constituting the most likely reason for poor outcome.…”
Section: Discussionmentioning
confidence: 52%
“…Adjuvant radiotherapy or chemotherapy depends on the degree of tumor distribution. 10,11 The most established theory for the etiopathogenesis of cancer is that the tumor begins as a solitary cell which has some features of that of the normal stem cells. 12,13 This cancer stem cells (CSCs) have an important role in tumor progression, recurrence, therapeutic resistance and metastasis in many types of cancers as pancreatic cancer, breast cancer and head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5 If primary SCC is not treated early and effectively, it often advances rapidly and results in high morbidity and mortality. 6,7 Owing to the low incidence of primary SCC, it is often discussed together with other histologic malignancies or metastatic SCC of the major salivary glands. Furthermore, most previous studies have included only a small number of primary SCC cases.…”
mentioning
confidence: 99%